Joint decision-making of production and maintenance in mixed model assembly systems with delayed differentiation configurations. Issue 13 (2nd July 2020) - Guo, Weihong; Gu, Xi
Abstract : Mixed model assembly systems (MMASs) can simultaneously manufacture multiple product variants and are developed to satisfy customers' increasing desire for products with a high variety. This paper investigates the joint decision-making of production and maintenance policies in MMASs with delayed differentiation configurations, where common operations are performed before differentiated processes. The problem is formulated as a Markov Decision Process (MDP) problem that minimises the average cost per unit time. Monte Carlo simulation is used to evaluate the system performance measures (e.g. volume mix ratio, product quality) under the optimal policy. Numerical examples are presented to illustrate the structure of the optimal policy and the impact of different factors on the system performance in an MMAS that produces two types of product variants. Techniques that can potentially solve the problem in large-sized MMASs are also discussed.